Prevalence of breast-feeding and exclusive breast-feeding at 48 h after birth and up to the sixth month in Cyprus: The BrEaST start in life project - Economou, Mary; Kolokotroni, Ourania; Paphiti-Demetriou, Irene; Kouta, Christiana; Lambrinou, Ekaterini; Hadjigeorgiou, Eleni; Hadjiona, Vasiliki; Tryfonos, Froso; Philippou, Elena; Middleton, Nicos (My University, 2018)
Objective To assess the prevalence and sociodemographic determinants of breast-feeding (BF) and exclusive breast-feeding (EBF) in Cyprus up to the sixth month. Design Cross-sectional and longitudinal descriptive study. BF and EBF were estimated based on mothers’ self-reported BF status in line with Step 7 of the WHO/UNICEF Baby-Friendly Hospital Initiative questionnaire and based on 24 h recall. Setting Maternity wards in all public hospitals and twenty-nine (of thirty-five) private maternity clinics nationwide. Subjects Consecutive sample of 586 mothers recruited within 48 h from birth, followed up by telephone interview at the first, fourth and sixth month. Results Although 84·3 % of mothers initiated BF before discharge, prevalence of BF at the sixth month was 32·4 %, with the highest reduction observed between the first and fourth months. Prevalence of EBF at 48 h was 18·8 % and fell gradually to 5·0 % at the sixth month. Mothers with higher educational attainment or higher family income were more likely to breast-feed until the sixth month. In terms of EBF, an association was observed only with education, which persisted until the sixth month. Other than social gradient, mode of delivery was the strongest determinant of BF initiation, exclusivity and continuation. Mothers who gave birth vaginally were three to four times more likely to initiate BF (OR=3·1; 95 % CI 1·7, 5·4) and EBF (OR=4·3; 95 % CI 2·7, 6·8). Conclusions The low prevalence of BF and EBF in Cyprus, together with the fact that caesarean section rates are currently among the highest in Europe, suggest the need for further research to understand this multidimensional phenomenon and for interdisciplinary policy action to protect, promote and support BF.
Keywords: Breast-feeding; Longitudinal; Prevalence; Sociodemographic determinants